1989
DOI: 10.1159/000185669
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Circulating Immune Complexes in the Classic Form of Hemolytic Uremic Syndrome: A Constant Finding

Abstract: In an attempt to further study the possible contribution of circulating immune complexes (CIC) in the pathogenesis of the classic form of hemolytic uremic syndrome, 9 patients were studied during the acute phase of the diseases. Clq solid-phase ELISA and conglutinin solid-phase ELISA, were used to measure the levels of immune complexes. All 9 were positive in one or both assays. No correlation was found between the levels of CIC and the clinical severity of the disease. The constant finding of positive CIC in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Furuse et al [6] later en countered CIC in 1 patient with sporadic HUS. Moreover, in a recent study we have found CIC as a constant finding in Accepted: February 18,1993 classical HUS, suggesting a probable immunopathogenic role [7].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Furuse et al [6] later en countered CIC in 1 patient with sporadic HUS. Moreover, in a recent study we have found CIC as a constant finding in Accepted: February 18,1993 classical HUS, suggesting a probable immunopathogenic role [7].…”
Section: Introductionmentioning
confidence: 80%
“…This technique has been previously reported [7,9]. The procedure used was basically that of C'asali et al [10] with minor changes.…”
Section: Introductionmentioning
confidence: 99%